PENGARUH PENERAPAN PROJECT BASED LEARNING MODEL PADA MATA PELAJARAN GREEN EDUCATION TERHADAP KEMAMPUAN BERPIKIR KREATIF VERBAL SISWA - Tina -; Nurul Istiqomah (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2019)
Project based learning model or PBL is a kind of learning model that organize learning which concern on project activity. Project activity give students independency to construct their knowledge and also engaging students in problems solving, so students will be more active in the learning process and able to develop students verbal creative thinking. The aim of this study was to analyze the effect of PBL model application of green education subject to the students creative verbal thinking. The research was conducted at SMA Al Muslim on May 2013. The method used was the quasi experiment research. Population was chosen by purposive sampling. The samples was chosen by simple random sampling were the XI Exact 2 grade students as experimental class and control class XI Exact 1 as much as 30 students. Instrumen used were test to the students creative verbal thinking and learning attainment observation sheets for experiment class and control class. The statistical calculation showed that the average score of students verbal creative thinking test of experimental class was 57.20, whereas the control group was 53.23. Test analysis used is the perquisite test from normality with the Kolmogorov-Smirnov test and homogeneity with F test. Based on calculations drived normally distribused data and homogeneous. The t test calculation showed that t calc > t table, (4.73 > 2.66) at Î± = 0.05, it was concluded that there is effect of PBL model on green education subject to the students verbal creative thinking of SMA Al Muslim.